Group of Pregnant Women: A Proposal for Health Promotion and Education - Castro Silvestre, Fernanda; Araújo Monteiro, Tiago (Archives of Business Research, 2022)
The present article seeks to show the benefit of the educational action with the pregnant women who were assisted in a Primary Health Care Unit in Fortaleza. The meetings took place monthly with the contribution and organization of a team of health professionals, addressing topics related to different spheres of pregnancy, such as: mental health, infectious diseases during pregnancy, clarification of doubts and myths related to pregnancy, in addition to health promotion by encouraging physical activity. The group made it possible to improve adherence and maintenance of follow-up in the treatment for syphilis, reducing sedentary lifestyle. There was also greater autonomy of the pregnant woman over the gestational period and better knowledge about the physiological body changes expected for that moment. Some difficulties were found, such as the withdrawal of some participants, the physical structure of the basic unit inadequate to accommodate the number of participants interested in the event and the late start of prenatal care, compromising the total effectiveness that the group could offer. Despite the difficulties, it can be seen that the group had a positive influence, contributing with information so that they could elaborate on their pregnancies, prevent themselves from the risk of infectious diseases and perform physical activities safely and previously guided by a health professional.